ON THE USE OF COMPUTER GAMES AT ENGLISH LESSONS - Ковальова, Т. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article studies the efficiency of the use of computer games at lessons for English language students. Reasons of change in the attitude to computer games are enumerated, the benefits of their use in education are highlighted, the results of using games at foreign language lessons are analyzed; methods of the use of certain computer games at English lessons are described as well. The problem analysis has shown that, considering present-day students’ interest in digital technologies, the direct use of parts or levels of computer games (or their indirect use by doing tasks related to the discussion or description of the main characters, plots and regulations of favorite games) at English lessons is appropriate as it will help involve all students in studying, increase their motivation for learning the language and practise it